Childhood trauma in schizophrenia spectrum disorder as compared to other mental health disorders. Issue 1 (2nd January 2017) - Mørkved, N.; Endsjø, M.; Winje, D.; Johnsen, E.; Dovran, A.; Arefjord, K.; Kroken, R. A.; Helle, S.; Anda-Ågotnes, L. G.; Rettenbacher, M. A.; Huber, N.; Løberg, E. M.
Abstract: Background : Childhood trauma (CT) is a potential risk factor in psychosis, and the prevalence of CT may be higher in patients with psychosis compared to other mental health disorders. The aim of the study was to investigate the potential specificity of CT in psychosis. Methods : The sample consisted of 52 patients with schizophrenia spectrum disorders and 52 matched patients with other mental health disorders. CT was measured by the CTQ-SF. The groups were compared on CTQ-SF sum and subscale scores indicating rates of CT, in addition to rates of none/low vs. moderate/severe levels of CT. Results : The psychosis group had significantly higher CTQ-SF sum scores, and reported significantly higher levels of, and more severe, physical and sexual abuse and physical neglect. Also, 67.3% of the psychosis group reported ≥ 1 CT above the cut-off, compared to 38.5% in the non-psychosis group. No patients in the non-psychosis group reported ≥ 4 CT, compared to 9.6% in the psychosis group. Conclusions : Patients with psychosis reported more severe and frequent CT compared to non-psychotic patients. Our results may indicate some specificity for moderate and severe levels of physical and sexual abuse, and physical neglect, in schizophrenia spectrum disorders.